Setting the scene for Innovative Air Mobility (IAM) services: a comparative study on citizens’ social acceptance through the experience factor - Almeida, H.; Kalakou, S.; Marques, C. (Transportation Research Symposium, 2025)
As a result of the many technological developments that have occurred recently Innovative Air Mobility (IAM) has emerged. The implementation of this new technology is planned for the next few years, and although it has enormous potential, it is crucial to explore and understand the opinion of citizens, thus social acceptance assumes a preponderant role. Considering that IAM is not currently available for use, this study focussed on evaluating the existence of differences in citizens' acceptance based on the format in which it is shown to individuals. Therefore, this comparative study aims to measure levels of social acceptance in order to understand whether experience interferes with citizens' perceptions of accepting a new technology. For this reason, three different experience groups were evaluated: (1) live demonstrations with drones in Greece and United Kingdom (N=150); (2) Virtual Reality environment with drones flying in Portugal (N=110); (3) watching a video about IAM in Portugal (N=145). To this purpose, acceptance was measured using a survey based on the literature. Thus, comparisons were made using hypothesis tests and correlational analyses. The acceptance values for the three different experiences were analysed and the results are discussed. Insights are extracted for the different form of collecting information on technology acceptance for innovations that are not yet available in the market, such as IAM. This study provides an assessment not only of the levels of social acceptance, a preponderant factor in the implementation of IAM, but also of the effect that the experience has on social acceptance, due to the manner in which it is presented to the public and that citizens' perceive this new technology. The present study sheds light on the influence that experience has on levels of acceptance in society, contributing to the deployment of this new technology.